Productivity of representative breeds of important cattle groups in Africa - Trail, J.C.M. (Australian Centre for International Agricultural Research, 1985)
Describes briefly the main ecological zones of Africa w. examples of the general types of cattle that can be maintained. Assesses the contributions of past research work in breed evaluation. Reports examples of breed characterization studies that highlight the value of such work for each of the three major indigenous cattle groups of Africa, viz, Africander, Tswana, & Tuli cattle of the Sanga group; Boran & small East African Zebu cattle of the humped zebu group; and N'dama and west African Shorthorn cattle of the Indigenous Taurine group.